Foreign Halal Packaged Products that Influence Purchase Intention - Arlisa, Berliana Rizki; Hendayani, Ratih; Ganesan, Yuvaraj (The Asian Journal of Technology Management (AJTM), 2019)
Abstract. Halal has become a major topic of conversation in the business world due to today's rapid development of halal packaged food production. This study discusses several factors that influence the purchasing decisions of Indonesian Muslim respondents on imported halal packaged food products. Halal awareness, Islamic brands and product ingredients have been predetermined as the influencing factors of purchase intention. As data source we use randomly distributed questionnaires to 107 Muslim respondents across the country. Our research shows that  the intention of Muslims to buy halal packaged food of foreign production was significantly affected by Halal Awareness and Islamic Brands. Meanwhile, the product ingredients factor was not proven to affect purchase intention. The findings of this study are expected to help inform foreign packaged food producers that they must certify their products with halal label and be more concerned about the halal appearance of their product packaging.Keywords: Halal packaged food, halal awareness, islamic brand, product ingredients, purchase intention